Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Model Pembelajaran Talking Stick pada SMA Negeri 4 Palangka Raya - Ervini Agustini; Supardi Supardi (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to describe learning activities and improve learning outcomes. The method used in this study is to use a Classroom Action Research (CAR) design that seeks to overcome the problems faced in the current situation. The subjects needed in this study were students of class XI-10 Palangkaraya 4 High School, totaling 35 students, for data collection techniques used were observation and tests. Data analysis consists of qualitative and quantitative data. The results of the study show that: (1) Student learning activities are good. This is evidenced by the acquisition of the average score of learning activities of students in the first cycle obtaining an average score of 3.77 with the criteria of Good. (2) There is an increase in learning outcomes. This can be proven by the acquisition of the average score of the students in the pre-cycle there is no complete (0.00%) got a value of unwilling 75 with unfavorable criteria. This is evidenced by the acquisition of the average score of learning activities of students in the first cycle obtaining an average score of 3.77 with completeness (100%) or getting a value of ≥ 75 with the criteria Good.